1999
DOI: 10.1046/j.1365-2265.1999.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial non‐medullary thyroid carcinoma: pathology review in 27 affected cases from 13 French families

Abstract: Micro familial non-medullary thyroid cancers are more common than previously reported and further studies are required to be able to distinguish this subgroup from sporadic papillary microcarcinomas. The careful pathological review of the familial non-medullary thyroid cancer in this study does not seem to point to a distinct subgroup of familial differentiated thyroid carcinoma although the data are intriguing. Genetic studies are now required to investigate this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 29 publications
1
28
2
2
Order By: Relevance
“…The low prevalence of FNMTC, together with small sampling series and short follow-up studies, has limited consistent information on patient survival as well. Some studies have reported distinct clinical behaviours (3,16,17,18,19,20,21), but others have claimed that there are no differences between the two entities (1,22,23,24,25). Our present data seem to support the latter view, as we did not observe, overall, statistical differences in clinicopathological features, DNA ploidy status and outcome measures between familial PTC (whole series) and sporadic PTC.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…The low prevalence of FNMTC, together with small sampling series and short follow-up studies, has limited consistent information on patient survival as well. Some studies have reported distinct clinical behaviours (3,16,17,18,19,20,21), but others have claimed that there are no differences between the two entities (1,22,23,24,25). Our present data seem to support the latter view, as we did not observe, overall, statistical differences in clinicopathological features, DNA ploidy status and outcome measures between familial PTC (whole series) and sporadic PTC.…”
Section: Discussioncontrasting
confidence: 38%
“…Although some studies have reported a less favourable prognosis for FNMTC (3,16,17,18,19,20,21), others did not verify this (1,22,23,24,25), and therefore, the biological and clinical behaviour of this familial disease, as compared with the much more frequent sporadic forms, remains a matter of controversy. Furthermore, data on molecular biomarkers, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Statistical estimates suggest that a grouping of two family members with NMTC could represent the concurrence of sporadic tumors, but thyroid tumors in three or more members in kindred, or the diagnosis of PTC in men and children, is more suggestive of a familial predisposition. [24][25][26][27][28][29][30][31][32][33][34][35][36][37]61 Although non-medullary thyroid cancer is mostly sporadic, evidence for a familial form, not associated with other Mendelian cancer syndromes described above (eg FAP and CS), is well documented and thought to cause more aggressive disease. The search for a genetic susceptibility locus for FNMTC started about a decade ago.…”
Section: -58mentioning
confidence: 99%
“…FNMTC patients have shorter disease-free survival than do sporadic disease patients because of frequent locoregional recurrence. [24][25][26][27][28][29][30][31][32][33][34][35][36][37]61 The genetic inheritance of FNMTC remains unknown, but it is believed to be an autosomal dominant mode with incomplete penetrance and variable expressivity. Genetic analyses of large FNMTC kindreds not only support the hypothesis of an inherited genetic predisposition to FNMTC, but also represent the first steps in identification of the putative susceptibility genes.…”
Section: -58mentioning
confidence: 99%
“…Do mesmo modo, a identificação dos genes responsáveis pelo CTNMF possivelmente facilitaria o rastreamento e o diagnóstico precoce da doença, aumentando as taxas de cura e de sobrevida. Analisando as várias famílias acometidas pelo CTNMF relatadas na literatura, observa-se acometimento de vários membros na mesma geração e transmissão por genitores de ambos os sexos (25)(26)(27)(28)(29)(30)(31), o que sugere transmissão genética por padrão de herança autossômico dominante, com penetrância variável.…”
Section: Genética Do Carcinoma Da Tiróide Não Medular Familiarunclassified